War against War!: pictures as means of social struggle in post-First World War Europe. Issue 4 (2nd October 2017) - Martini, Michele
Abstract : Germany 1925: Ernst Friedrich, a young anarchist and anti-militarist activist, publishes one of the first independent books composed only of photographs and captions: War against War! His stated goal is to employ classified pictures of the First World War (WWI) to unmask nationalistic propaganda and expose the false narratives of militaristic rhetoric. Published on the eve of the golden age of photojournalism, this book is the first grassroots attempt to use photography as a means of social and cultural change on a large scale. Through in-depth analysis of some key pictures, I will investigate the relation this series of images establishes with the beholder and the role it plays in shaping his visual experience. Emphasis will be placed on 24 close-ups of disfigured faces which constitute the last set of this visually driven narrative. As I will seek to demonstrate, the complex array of pictures created by Ernst Friedrich testifies to a fundamental yet still embryonic change in the social perception of photography in the post-WWI Europe.